Diphtheria Toxin‐ and GFP‐Based Mouse Models of Acquired Hypoparathyroidism and Treatment With a Long‐Acting Parathyroid Hormone Analog. (20th January 2016) - Bi, Ruiye; Fan, Yi; Lauter, Kelly; Hu, Jing; Watanabe, Tomoyuki; Cradock, Jim; Yuan, Quan; Gardella, Thomas; Mannstadt, Michael
ABSTRACT: Hypoparathyroidism (HP) arises most commonly from parathyroid (PT) gland damage associated with neck surgery, and is typically treated with oral calcium and active vitamin D. Such treatment effectively increases levels of serum calcium (sCa), but also brings risk of hypercalciuria and renal damage. There is thus considerable interest in using PTH or PTH analogs to treat HP. To facilitate study of this disease and the assessment of new treatment options, we developed two mouse models of acquired HP, and used them to assess efficacy of PTH(1–34) as well as a long‐acting PTH analog (LA‐PTH) in regulating blood calcium levels. In one model, we used PTHcre‐iDTR mice in which the diphtheria toxin (DT) receptor (DTR) is selectively expressed in PT glands, such that systemic DT administration selectively ablates parathyroid cells. For the second model, we generated GFP‐PT mice in which green fluorescent protein (GFP) is selectively expressed in PT cells, such that parathyroidectomy (PTX) is facilitated by green fluorescence of the PT glands. In the PTHcre‐iDTR mice, DT injection (2 × 5 μg/kg, i.p.) resulted in moderate yet consistent reductions in serum PTH and sCa levels. The more severe hypoparathyroid phenotype was observed in GFP‐PT mice following GFP‐guided PTX surgery. In each model, a single subcutaneous injection of LA‐PTH increased sCa levels more effectively and for a longer duration (>24 hours) than did a 10‐fold higher dose of PTH(1–34), without causing excessive urinary calcium excretion. These new mouse models thus faithfully replicate two degrees of acquired HP, moderate and severe, and may be useful for assessing potential new modes of therapy. © 2015 American Society for Bone and Mineral Research.